A phytochemical survey at Ulu Endau Johore Malaysia - Kiew, Ruth; Lajis, Nordin; Anthonysamy, Samy; Bakar, Ismail; Lim, C. G.; Yusuf, Omar; Ravindran, A.; Salam, Mohd Razali (Malaysian Nature Society, 1987)
118 species were screened for alkaloids, saponins and triterpenes/steroids. About 60 percent of these species had not been screened before. Eight species contained alkaloids of which four species, Psychotria rostrata, Uncaria callophylla, U. longiflora var. pteropoda (Rubiaceae) and Clerodendron laevifolium (Verbenaceae) gave a strong positive reaction. 31 species contained saponins of which 13 gave a strong positive reaction, Thottea grandiflora (Aristolochiaceae), Vatica hullettii (Dipterocarpaceae), Didymocarpus falcatus (Gesneriaceae), Pachycentria constricta, Phyllagathis cordata (Melastomataceae), Aglaia meliosmoides (Meliaceae), Tristania whitiana (Myrtaceae), Pentaphragma horsfieldii (Pentaphragmataceae), Gaertnera griffithii, Psychotria griffithii, Uncaria callophylla, Urophyllum ferrugineum (Rubiaceae) and Clerodendron laevifolium (Verbenaceae). Sixty species gave a positive reaction for triterpenes/steroids.